Odpowiedź :
ײ:2x⁻³=1/2x⁵
(-2a³)⁴+(-2a⁴)³-(-3a⁶)²+(a₂)⁵=16a¹²-8a¹²-9a¹²+a¹°=-a¹²+a¹⁰
(1½)⁻⁴:(1½)⁻⁶=(1½)²=9/4
(0,2)⁵.(2½)⁵=(5/2*5/2)⁵=(25/4)⁵
(-2a³)⁴+(-2a⁴)³-(-3a⁶)²+(a₂)⁵=16a¹²-8a¹²-9a¹²+a¹°=-a¹²+a¹⁰
(1½)⁻⁴:(1½)⁻⁶=(1½)²=9/4
(0,2)⁵.(2½)⁵=(5/2*5/2)⁵=(25/4)⁵
(-2a³)⁴+(-2a⁴)³-(-3a⁶)²+(a₂)⁵= (-2a)12 + (3a) 12 + a10= a12 + a10= a2
kumasz o co chodzi?? ; dd
(1½)⁻⁴:(1½)⁻⁶= (1½)-2 = 1/(3)-2 / 2= 1/3
(0,2)⁵.(2½)⁵=(5/2*5/2)⁵= (02/10)5 * (5/2)5= (1/2)5
a w tym pierwszym to 2x do -3 to czasem nie jest w nawiasie?
kumasz o co chodzi?? ; dd
(1½)⁻⁴:(1½)⁻⁶= (1½)-2 = 1/(3)-2 / 2= 1/3
(0,2)⁵.(2½)⁵=(5/2*5/2)⁵= (02/10)5 * (5/2)5= (1/2)5
a w tym pierwszym to 2x do -3 to czasem nie jest w nawiasie?